Cerebral Oxygen Metabolism in Neonatal Hypoxic Ischemic Encephalopathy during and after Therapeutic Hypothermia. Issue 1 (January 2014) - Dehaes, Mathieu; Aggarwal, Alpna; Lin, Pei-Yi; Rosa Fortuno, C; Fenoglio, Angela; Roche-Labarbe, Nadège; Soul, Janet S; Franceschini, Maria Angela; Grant, P Ellen
Pathophysiologic mechanisms involved in neonatal hypoxic ischemic encephalopathy (HIE) are associated with complex changes of blood flow and metabolism. Therapeutic hypothermia (TH) is effective in reducing the extent of brain injury, but it remains uncertain how TH affects cerebral blood flow ( CBF ) and metabolism. Ten neonates undergoing TH for HIE and seventeen healthy controls were recruited from the NICU and the well baby nursery, respectively. A combination of frequency domain near infrared spectroscopy (FDNIRS) and diffuse correlation spectroscopy (DCS) systems was used to non-invasively measure cerebral hemodynamic and metabolic variables at the bedside. Results showed that cerebral oxygen metabolism ( CMRO 2i ) and CBF indices ( CBF i ) in neonates with HIE during TH were significantly lower than post-TH and age-matched control values. Also, cerebral blood volume ( CBV ) and hemoglobin oxygen saturation ( SO 2 ) were significantly higher in neonates with HIE during TH compared with age-matched control neonates. Post-TH CBV was significantly decreased compared with values during TH whereas SO 2 remained unchanged after the therapy. Thus, FDNIRS–DCS can provide information complimentary to SO 2 and can assess individual cerebral metabolic responses to TH. Combined FDNIRS–DCS parameters improve the understanding of the underlying physiology and have the potential to serve as bedside biomarkers of treatment response and optimization.